2005
DOI: 10.1002/pmic.200401227
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis reveals adaptation ofPseudomonas aeruginosa to the cystic fibrosis lung environment

Abstract: Pseudomonas aeruginosa is known for the chronic lung colonization of cystic fibrosis (CF) patients in addition to eye, ear and urinary tract infections. With the underlying disease CF patients are predisposed to P. aeruginosa chronic lung infection, which leads to morbidity and mortality. In this study, we compared the protein expression profile of a CF lung-adapted P. aeruginosa strain C with that of the burn-wound isolate PAO. Differentially expressed proteins from the whole-cell, membrane, periplasmic as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 54 publications
(26 reference statements)
2
54
0
Order By: Relevance
“…We have revealed that the P. aeruginosa PhoPQ system is upregulated during adherence to epithelial cells, as are a number of genes known to be PhoQ or Mg 2ϩ regulated, suggesting that PhoPQ may partially control the adaptation of P. aeruginosa to epithelial surfaces. Several studies have identified phoQ mutations in polymyxin-resistant clinical isolates from both acute and chronic infections (4,43,57,61). Since the PhoPQ system is transcriptionally upregulated upon adherence of the WT to epithelial cells, it is possible this contributes to early adaptations to the lung environment that are later stabilized by a mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have revealed that the P. aeruginosa PhoPQ system is upregulated during adherence to epithelial cells, as are a number of genes known to be PhoQ or Mg 2ϩ regulated, suggesting that PhoPQ may partially control the adaptation of P. aeruginosa to epithelial surfaces. Several studies have identified phoQ mutations in polymyxin-resistant clinical isolates from both acute and chronic infections (4,43,57,61). Since the PhoPQ system is transcriptionally upregulated upon adherence of the WT to epithelial cells, it is possible this contributes to early adaptations to the lung environment that are later stabilized by a mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Several virulence factors have been characterized for P. aeruginosa; however, their expression and contributions to CF lung disease are still for the most part incompletely defined. It was previously observed in CF that many of the virulence factors proposed to be essential for establishing a lung infection are actually downregulated or lost during the progression to a chronic infection (13,16,51,59,61). Notable bacterial factors that are required for the initial colonization of the lungs but that are downregulated or lost in chronic CF isolates include flagella, pili, proteases, and smooth lipopolysaccharide (LPS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E. Smith et al, 2006;Sriramulu et al, 2005). These changes cause bacteria to diversify and to exhibit characteristics differing from isolates found in the environment outside the body.…”
Section: Pathogenesis Of P Aeruginosa In Cfmentioning
confidence: 99%
“…The secretory proteome (secretome) of clinical strains of P. aeruginosa is known to contain a number of proteases other than LasB, including the elastolytic metalloprotease LasA and the Ser proteinase PrpL (or protease IV) (10,49). In order to establish whether or not LasB was uniquely responsible for the cleavage of uPAR, we compared the proteolytic capacity of the secretome from the LasB-producing strain PAO1 to that of the LasB-deficient strain PDO240, designed on the PAO1 genetic background (37).…”
Section: Soluble Upar Is Cleaved By Lasb Within Both the D1-d2mentioning
confidence: 99%